Fast integrated spectra analyzer (FISA): a new computational tool for age and reddening determination of small angular diameter open clusters using integrated spectroscopy - Benítez Llambay, Alejandro (2012)
We present a new algorithm called “Fast Integrated Spectra Analyzer” (FISA) that permits fast and reasonably accurate age and reddening determinations for small angular diameter open clusters by using their integrated spectra in the (3600–7400) Å range and currently available template spectrum libraries. This algorithm and its implementation help to achieve astrophysical results in shorter times than from other methods. A brief review is given of the integrated spectroscopic technique applied to the study of open clusters, as well as the basic assumptions that justify its use. We describe the numerical algorithm employed in detail, show examples of its application, and provide a link to the code. Our method has successfully been applied to integrated spectroscopy of open clusters, both in the Galaxy and in the Magellanic Clouds, to determine ages and reddenings.